2021
DOI: 10.1136/jitc-2021-002883
|View full text |Cite
|
Sign up to set email alerts
|

BT7480, a novel fully synthetic Bicycle tumor-targeted immune cell agonist™ (Bicycle TICA™) induces tumor localized CD137 agonism

Abstract: BackgroundCD137 (4-1BB) is an immune costimulatory receptor with high therapeutic potential in cancer. We are creating tumor target-dependent CD137 agonists using a novel chemical approach based on fully synthetic constrained bicyclic peptide (Bicycle®) technology. Nectin-4 is overexpressed in multiple human cancers that may benefit from CD137 agonism. To this end, we have developed BT7480, a novel, first-in-class, Nectin-4/CD137 Bicycle tumor-targeted immune cell agonist™ (Bicycle TICA™).MethodsNectin-4 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…As the lead Bicycle TICA candidate, BCY11863 was more extensively profiled in vitro and in vivo. 24 In additional studies using the CT26 model described earlier, it was observed that the antitumor activity for BCY11863 could be achieved even when dosed Q3D. 24 This indicated that a positive pharmacologic effect with Bicycle TICAs can be achieved without sustained plasma concentrations, which is markedly different from the exposure approaches taken with the recombinant bispecific CD137 agonists currently under clinical development.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the lead Bicycle TICA candidate, BCY11863 was more extensively profiled in vitro and in vivo. 24 In additional studies using the CT26 model described earlier, it was observed that the antitumor activity for BCY11863 could be achieved even when dosed Q3D. 24 This indicated that a positive pharmacologic effect with Bicycle TICAs can be achieved without sustained plasma concentrations, which is markedly different from the exposure approaches taken with the recombinant bispecific CD137 agonists currently under clinical development.…”
Section: Resultsmentioning
confidence: 99%
“… 24 In additional studies using the CT26 model described earlier, it was observed that the antitumor activity for BCY11863 could be achieved even when dosed Q3D. 24 This indicated that a positive pharmacologic effect with Bicycle TICAs can be achieved without sustained plasma concentrations, which is markedly different from the exposure approaches taken with the recombinant bispecific CD137 agonists currently under clinical development. The reasonably short-circulating half-life of BCY11863 in mice ( Figure 8 B, 2.3 h after IP injection) therefore permits a further exploration of the effect of intermittent plasma exposure on antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations